2021
DOI: 10.1038/s41467-021-21925-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulating electron density of vacancy site by single Au atom for effective CO2 photoreduction

Abstract: The surface electron density significantly affects the photocatalytic efficiency, especially the photocatalytic CO2 reduction reaction, which involves multi-electron participation in the conversion process. Herein, we propose a conceptually different mechanism for surface electron density modulation based on the model of Au anchored CdS. We firstly manipulate the direction of electron transfer by regulating the vacancy types of CdS. When electrons accumulate on vacancies instead of single Au atoms, the adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(173 citation statements)
references
References 54 publications
3
169
0
1
Order By: Relevance
“…Electronic structures of catalysts are crucial to the overall catalytic process. [28][29][30] The adsorption bond strength of reactants or intermediates, the charge kinetics and the catalyst activity have been proven to be highly related to the characteristics of the surface electronic structure of catalysts. 31,32 Aer the metal SAs are anchored or coordinated with the support, the strong metalsupport interaction can regulate the electronic structures of SAs due to the redistribution of charge density.…”
Section: Modulated Electronic Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic structures of catalysts are crucial to the overall catalytic process. [28][29][30] The adsorption bond strength of reactants or intermediates, the charge kinetics and the catalyst activity have been proven to be highly related to the characteristics of the surface electronic structure of catalysts. 31,32 Aer the metal SAs are anchored or coordinated with the support, the strong metalsupport interaction can regulate the electronic structures of SAs due to the redistribution of charge density.…”
Section: Modulated Electronic Structuresmentioning
confidence: 99%
“…36 For solar-to-chemical energy conversion, Zhou et al found that the deployment of Au SAs in Cd 1Àx S modulated the electronic structures of Au atoms, which could promote the charge transfer and offer sufficient electrons for photocatalytic CO 2 reduction reaction. 30 In another case, band engineering of Pt II -C 3 N 4 photocatalysts by introducing Pt SAs was proven to be an efficient solution to modify the band energy levels and shi the valence band maximum level to promote water oxidation. 37 Similarly, rational design of Ta 3 N 5 photoanodes by gradient Mg doping could improve the PEC water oxidation performance due to band engineering.…”
Section: Modulated Electronic Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…由于金属原子普遍存在聚集的趋势, 因此, 该领域最关 键的挑战是探索一种有效的方法来牢固地锚定金属单 原子, 从而为所需的催化反应形成高度稳定和反应性的 催化活性中心 [4] . 与贵金属单原子催化材料(如金、铂、 铱、钯等)相比 [5][6][7][8] , 非贵金属催化材料以其丰富的储量, 便宜的价格, 大大降低了成本 [9] . 其中, 铜单原子催化 材料在温和条件下表现出很高的催化性能, 被认为是最 有前途的替代品之一 [10][11][12] , 因而得到了越来越多的关 注.…”
Section: 引言unclassified
“…reported that the direction of photogenerated electron transfer could be controlled by adjusting the vacancy type of CdS. [ 17 ] Gao et al. grew S‐vacancy ZnS vertically on the Zn‐In‐LDH surface, which stimulated the synergistic effect of vacancy and 2D interface and improved the performance of photocatalytic hydrogen production.…”
Section: Introductionmentioning
confidence: 99%